Compliance: mecanismos de controle interno - Silva, Renan Boccacio Souza da (Universidade do Vale do Rio dos Sinos, 2015)
Internal control mechanisms, also known as compliance programs, are essential tools to reduce and avoid the risks that illicit acts be practiced within companies. These programs offer a range of mechanisms that help reduce hidden costs. When effective implemented, they reduce informational asymmetry and agency problems, maximize profits and improve business through more efficient decision making.
Keywords: Mecanismos internos; Programas de compliance; Problemas de agência e assimetria informacional; Mechanism of internal control; Compliance programs; Agency problems and informational asymmetry